IMPLEMENTASI PENGGUNAAN LIMA BAHASA CINTA DI SEKOLAH DASAR - Hendi Hendi; Fajri Ismail; Muhammad Win Afgani (CV. ADIBA AISHA AMIRA, 2023)
This paper aims to describe and examine more deeply the use of the five languages of love in elementary schools.. This paper uses the library research method by critically and in-depth examining relevant library materials such as books and journals that are appropriate to be used as references in the preparation of this paper. The data collection technique used in this paper uses secondary data, namely by collecting data indirectly by examining the object in question. The results of this study indicate that this language of love is a medium and a means to communicate with children or students. It can also increase student potential, educate with love and be smart, and can arouse children's curiosity.